Effect of Salvadora persica on reproductive behavior in rats exposed to cigarette smoke - Syed Imam Rabbani (GarVal Editorial Ltda., 2019)
Context: The components of cigarette smoke are known to adversely affect the reproductive behavior in men and women. Salvadora persica commonly used in oral hygiene, was found to exhibit lipid lowering, hypoglycemic, anti-ulcer, anti-depressant activities. Aims: To evaluate the effect of Salvadora persica on reproductive behavior in rats exposed to cigarette smoke. Methods: The lyophilized decoction of S. persica was administered daily for four weeks by oral route at three doses (50, 100 and 200 mg/kg) to eight-weeks' cigarette smoke-exposed rats. Reproductive behavior in male rats was recorded by the number of approaches, mounts and intromission while in the female it was done by the number of approaches and escape frequency to male approach. Relative weights of testis and ovaries were determined. Ginseng at 100 mg/kg was used as a standard aphrodisiac. The results were analyzed statistically by one-way ANOVA followed by Tukey test. p<0.05 was considered to indicate the significance of results. Results: The results indicated that tobacco smoke exposure adversely affected the reproductive behavior in both male and female rats, besides increasing the relative weights of testis/ovaries. Among the tested doses, only the highest dose of S. persica (200 mg/kg) produced significant (p<0.05) increase in number of approach, frequency of mounts and latency of intromission but also significantly (p<0.05) enhanced the relative weight of testis and reduced the relative weight of ovaries in cigarette smoked animals. The marginal improvement in the reproductive behavior could be related to the phytoconstituents of the decoction. Ginseng, on the other hand, produced significant aphrodisiac activity and reversed the changes in the relative weights of the reproductive organs induced by cigarette smoke. Conclusions: The observation suggests that decoction of S. persica improved some of the parameters of male reproductive behavior but the role of the drug on the reproductive organs needs further investigation.